From the history of the post-war researches on popular culture and literature - Mazurkiewicz, Adam (Interdyscyplinarium nauk o mediach i kulturze, 2020)
The aim of the article was to present how the researchers’ approach to the issues of popular culture and literature changed after 1945. The author focuses on the effect that the socio-political and market conditions had on perceiving pop culture and literature. For the purposes of clarity, in the article the period beginning from 1945 was divided into subperiods, each marked by specific tendencies which had the greatest impact on public imagination and on understanding the role that the circulation of popular culture had in social life. At the same time, one can easily notice the development of reflection over the popular culture, which finally leads to depriving it of any function in the times of socialist realism (1949–1956): from accepting some of its indications and simultaneous understanding it in terms of ideology (1957–1990), to strong tendencies of treating pop-cultural creations as a proof of cultural changes of the modern world – especially visible in the latest researches.